IECON 2019 - 45th Annual Conference of the IEEE Industrial Electronics Society 2019
DOI: 10.1109/iecon.2019.8927087
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Multiport Converter as Cost Efficient Solution for DC-Fast Charger of Electric Vehicle

Abstract: The ongoing electrification of the transport sector raises demands for new power electronic solutions. As a consequence, modular converter structures are state of the art for fast charging, since high power and short charging times are required. This work presents a modular multiport DC-DC converter which has the capability to decrease the cost and size of the required charging station. Furthermore, design guidelines for the investigated topology are presented. The analysis is validated with a three port isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The placement of the coupling inductors in TBDC also affects its performance and it has been suggested in the literature [19] that impedance of the output bridge should be larger than that of transformer primary. It has also been suggested that placing external inductors on secondary side yields a better performance than placing on all ports or on the primary alone.…”
Section: Comparison Of Multiple Battery Integration With Dab Modular mentioning
confidence: 99%
See 4 more Smart Citations
“…The placement of the coupling inductors in TBDC also affects its performance and it has been suggested in the literature [19] that impedance of the output bridge should be larger than that of transformer primary. It has also been suggested that placing external inductors on secondary side yields a better performance than placing on all ports or on the primary alone.…”
Section: Comparison Of Multiple Battery Integration With Dab Modular mentioning
confidence: 99%
“…It has also been suggested that placing external inductors on secondary side yields a better performance than placing on all ports or on the primary alone. The first configuration requires small phase shifts to maintain the two output ports at equal voltages if one port voltage changes due to the variation of the other port voltage [19,20]. (d) Requirement of magnetics: Reduction in the core mean length in TBDC toplogy results in core volume reduction and correspondingly core cost reduction by one-fourth times compared to the conventional system (14).…”
Section: Comparison Of Multiple Battery Integration With Dab Modular mentioning
confidence: 99%
See 3 more Smart Citations